2021
DOI: 10.1155/2021/6852867
|View full text |Cite
|
Sign up to set email alerts
|

Plant-Derived Chinese Medicine Monomers on Ovarian Cancer via the Wnt/β-Catenin Signaling Pathway: Review of Mechanisms and Prospects

Abstract: Ovarian cancer (OC) is a common malignant tumor of the female reproductive system and has a high morbidity and mortality rate. The progression and metastasis of OC are complex and involve multiple signaling pathways. The Wnt/β-catenin signaling pathway is closely related to OC, and therefore blocking the activation of the Wnt/β-catenin signaling directly or inhibiting related genes, and molecular targets is of great value in treating OC. Toxicities such as myelotoxicity, cardiotoxicity, genotoxicity, and vasos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 83 publications
1
5
0
Order By: Relevance
“…We therefore considered that the molecular mechanism of ACY1-regulated cetuximab resistance in CRC was related to the Wnt signaling pathway. As expected, our results revealed that the expression of β-catenin, a key protein in the Wnt/β-catenin pathway, was significantly decreased with increasing radiation dose, while the levels of E-cadherin, a downstream protein in the Wnt/β-catenin pathway and a marker of tumor migration [ 52 , 53 ], were significantly increased. Finally, we found that the levels of E-cadherin were further increased, and the levels of β-catenin were further decreased in ACY1-downregulated HCT116-R cells after irradiation.…”
Section: Discussionsupporting
confidence: 82%
“…We therefore considered that the molecular mechanism of ACY1-regulated cetuximab resistance in CRC was related to the Wnt signaling pathway. As expected, our results revealed that the expression of β-catenin, a key protein in the Wnt/β-catenin pathway, was significantly decreased with increasing radiation dose, while the levels of E-cadherin, a downstream protein in the Wnt/β-catenin pathway and a marker of tumor migration [ 52 , 53 ], were significantly increased. Finally, we found that the levels of E-cadherin were further increased, and the levels of β-catenin were further decreased in ACY1-downregulated HCT116-R cells after irradiation.…”
Section: Discussionsupporting
confidence: 82%
“…Along with safety concerns, it is also difficult to meet clinical needs [ 19 21 ]. Pilot studies have shown that TCM, including MAP 30 and Paclitaxel, has been extensively applied to treat ovarian cancer effectively [ 8 10 , 14 ]. However, despite extensive clinical research, the clinical efficacy of TCM is still not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence-Based Complementary and Alternative Medicine [8][9][10]14]. However, despite extensive clinical research, the clinical efficacy of TCM is still not well understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditional Chinese medicine has a multi-target, multi-pathway compound effect and its monomer preparations are characterized by small side effects and significant therapeutic effects ( 8 ). Such features allow the treatment of ischemic stroke by traditional Chinese medicine to have great potential for its application in a wide range of diseases.…”
Section: Introductionmentioning
confidence: 99%